Substitution of fish meal in diets for marine shrimp grown in a biofloc system - Scopel, Bruno Ricardo; Schveitzer, Rodrigo; Seiffert, Walter Quadros; Pierri, Vinicius; Arantes, Rafael da Fonseca; Vieira, Felipe do Nascimento; Vinatea, Luis Alejandro (Pesquisa Agropecuaria Brasileira, 2011)
The objective of this work was to evaluate the substitution of two fish meal inclusion levels by other ingredients, in the diets of Litopenaeus vannamei reared in a biofloc system. The following diets were evaluated: without fish meal (diet A, 100% replacent), with addition of 12.5% of fish meal (diet B, 40% replacent), and a control diet with addition of 21% (diet C, 0% replacent). In diets A and B, soybean meal and meat and viscera meals were the main protein replacement. The performance indexes of shrimps and the physical and chemical parameters of water were analyzed. Shrimp fed diet B had higher final weight (11.63±1.38 g), compared to shrimp fed a diet A (9.39±0.31 g final weight) or C (10.20±1.10 g final weight). The other parameters of performance such as yield, feed conversion and survival did not differ between treatments. The reduction of fish meal by 40.0% can be done in a L. vannamei superintensive biofloc system without interfering on their growth performance or on the water quality of the culture.